Impact of the COVID-19 Pandemic on Pediatric Acute Appendicitis - Ocampo Anduaga, Edward (2024)
Background: The COVID-19 pandemic implied the modification of the entire healthcare system including paediatric surgical practice, with delays in diagnosis and increased morbidity. The aim of the study was to analyze its influence on the rate of perforated appendicitis and its complications in children during the first 9 months of the pandemic compared to the same period of the previous year. Methods: Observational, cross-sectional analytical study; included patients younger than 15 years with acute appendicitis who required emergency surgery during the periods from April to December 2019 (pre-pandemic group) and April to December 2020 (pandemic group). The rate of perforated appendicitis in each group was analyzed, as well as postoperative complications, hospital stay, readmissions, associated symptoms and demographic variables. Results: There were 108 patients included in each cohort, there were no significant differences in age (p = 0.799), sex (p = 0.165) or associated symptoms such as abdominal pain (p = 0.783), fever (p = 0.890), nausea/vomiting (p = 0.784) and diarrhea (p = 0.685). The proportion of perforated appendicitis was 39.8% in the pandemic group and 34.3% in prepandemic (p = 0.398). No differences were found in postoperative complications (p = 0.394), hospital stay (p = 0.189) or readmissions (p = 0.249). Conclusions: The incidence of perforated appendicitis and complications of appendectomy in children was not modified by the COVID-19 pandemic.